Supporting patients with low health literacy: what role do radiation therapists play? - Smith, S.; Zhu, Y.; Dhillon, H.; Milross, C.; Taylor, J.; Halkett, Georgia; Zilliacus, E. (Springer-Berlin, 2013)
Purpose: Health literacy plays a key role in a patient’s ability to use health information and services, and can affect health outcomes. This study aimed to explore radiation therapists’ perspectives on how they support people with lower health literacy who are undergoing radiotherapy. Methods: Semi-structured interviews were conducted with 25 radiation therapists working in radiation oncology departments in New South Wales, Australia. Results: The four key themes were (1) the process of identifying a patient with low health literacy, (2) the perceived consequences of low health literacy, (3) managing and responding to the needs of different health literacy groups and (4) recommendations to address low health literacy in radiotherapy. Radiation therapists appeared to make an informal, intuitive judgment about a patient’s health literacy, using a variety of verbal and non-verbal cues as well as impromptu conversations with the multi-disciplinary team. Patients perceived to have lower health literacy were described as having greater difficulties assimilating knowledge and engaging in self-care. Although participants reported communicating to patients at a basic level initially, they subsequently tailored their communication to match a patient’s health literacy. Strategies reported to communicate to low health literacy groups ranged from using lay language with minimal medical terminology, using visual aids (photos), using analogies, reiterating information and asking family members with higher literacy to attend consultations. Conclusion: A more structured approach to supporting patients with low health literacy and integrating health literacy training in radiation oncology departments may help to minimise the adverse outcomes typically experienced by this population.